Analysis Of The Pattern Of Education For Persons With Disabilities In Law Number 20 Of 2003 Concerning The National Education System - Zamrony ABDUSSAMAD; Sudarsono SUDARSONO; Imam KOESWAHYONO; Istislam ISTISLAM (Indonesia Strategic Sustainability, 2022)
Inclusive education has many different meanings and interpretations. There is still some uncertainty about the difference between inclusive and special education for individuals with disabilities, sometimes known as special schools (SLB). Meanwhile, the term inclusive education is not known in the National Education System Law, which uses the term